Biliary complications after living donor hepatectomy: A first report from India. Issue 5 (26th April 2016) - Pamecha, Viniyendra; Bharathy, Kishore Gurumoorthy Subramanya; Kumar, Senthil; Sasturkar, Shridhar Vasantrao; Sinha, Piyush Kumar
Abstract : Biliary complications after donor hepatectomy can result in significant morbidity. We herein present our experience of donor hepatectomy, highlighting surgical techniques that prevent complications. Data were reviewed from a prospectively maintained database of all donors who underwent hepatectomy from April 2011 to April 2015. Standard operative technique as described was followed in all patients. Biliary complications and morbidity were recorded and stratified as per Clavien‐Dindo classification. Results were compared with published literature. During the study period, 160 donors underwent hepatectomy. The majority of the graft types were right hemiliver without the middle hepatic vein (71.9%). Major complications (grade III and above) occurred in 5.6% of the donors. There was no donor mortality. Only 1 out of the 160 donors (0.6%) has had a grade III biliary complication requiring endoscopic retrograde cholangiography and papillotomy. There were 3 grade II biliary complications, all occurring after left lateral sectionectomy, necessitating prolonged retention of the intra‐abdominal drain. The median duration of hospital stay was 11 days (range, 5‐67 days), and the duration of follow‐up was 16 months (range, 3‐52 months). There was no loss to follow‐up, and no donor required readmission or outpatient procedures for any biliary complication. In conclusion, with careful donor selection and a standardized surgical technique, biliary complications can be minimized. Liver Transplantation 22 607‐614 2016 AASLD.